Treatment-related changes towards normalization of the abnormal external signal processing in panic disorder. - Christian Valt; Dorothea Huber; Birgit Stürmer (PLoS ONE)
Despite the scientific consensus on the efficacy of psychotherapy for the treatment of psychological disorders, the evidence of treatment-related changes towards normalization of abnormal brain functions in patients is mixed. In the present experiment, we investigated whether treatment can affect early information processing, by testing abnormal event-related potentials (ERPs) evoked by internal and external signals in panic disorder. Sixteen patients with panic disorder and comorbid personality disorder and sixteen control participants performed a response-choice task and a passive viewing task in two testing sessions, separated by around 14 months. During this period, patients received psychological treatment. In agreement with previous studies of performance monitoring, the abnormal amplitude of the Ne/ERN-an index of error processing based on internal signals-did not change between the first and second testing session. However, treatment-related changes were evident for the abnormal vertex positive potential (VPP) evoked by external signals in the response-choice task and the passive viewing task. In patients, the VPP was smaller in the second session compared to the first session, whereas no significant changes occurred in controls. This result supplies evidence of treatment-related changes towards normalization in the early information processing of external visual stimuli in panic disorder.